ANALISIS FRAMING PEMBERITAAN KONTROVERSI PENYELENGGARAAN MISS WORLD 2013 PADA KOMPAS.COM DAN THE NEW YORK TIMES ONLINE - Virgitta Septyana (Universitas Bunda Mulia, 2014)
Indonesia selected as a host of the beauty pageant contest which is the oldes in the world, called Miss World. Various rallies to protest against the suspension of the holding of Miss Wolrd emerged. The extrimists, which are Forum Umat Islam, Front Pembela Islam, Majelis Mujahiddin Indonesia considers this beauty pageant as the pornography event. Researchers want to see how presentation of the news content by two media, namely Kompas.com and The New York Times Online in preaching the controversy of Miss World 2013. Researcher used concepts and theories that associated with this research, which are event, mass media, news, framing, and agenda setting.Researchers conducting the framing analysis by Robert N. Entman by doing the five stages of framing. Through framing analysis, the proclamation can be viewed as an attempt to influence the audiences.Conclusions from this research revealed that the news on Kompas.com and The New York Times Online against the holding of the Miss World controversy in Indonesia tends to be negative. Each of the media see that there is a fear from Government of Indonesia against the extrimists and also the extrimists are keep fighting against the decision that has been made by Government of Indonesia. Key Words: Controversy, Media, Framing, Communication